O09-5 The italian survey on perception of health at work: the association of working conditions and occupational risks perception with workers' health. (1st September 2016) - Russo, Simone; Ronchetti, Matteo; Tecco, Cristina Di; Persechino, Benedetta; Iavicoli, Sergio
Abstract : Background: The last decades have seen significant developments in the economic, political, technological and social landscape as well as in the nature of work that has been re-shaped under these impacts. All these changes have had a high impact on workers' health and have lead to several improvements in occupational health and safety (OSH) policy framework at European and national level. The Italian Workers' Compensation Authority (INAIL) carried out a national survey (Insula project) to investigate the employer's perception related to working conditions, occupational risk exposure and their impact on mental and physical health. This study aimed to provide secondary analysis of INSuLa data to investigated factors mainly associated to workers' health in a national wide representative sample of workers. Methods: A questionnaire has been developed and administered to a sample of 8, 000 workers (representative of the Italian working population in companies with more than 5 employees) through CATI interview; a set of logistic and linear regression models were adopted to test effects of the variables on mental and physical health. Results: mental and physical health resulted to be positively linked with peer support (p<0.01, exp(B)=1.26) and job satisfaction (p<0.05, exp(B) = 1.23) and negatively linked with workplace violence and harassment (p<0.001, exp(B) = 1.57); the perception of OSH risks (p < 0.001, exp(B) = 0.75) and work-related stress risk exposure (p < 0.05, exp(B) = 0.98) reported negative relationships with mental and physical health and a positive relationship with depression. working conditions (p<0.05) – except for organisational change – were negative related with depression. Conclusions: This study offers a secondary analysis of Insula project that represents a unique case in Italy in terms of the sample's dimensions and workforce representativeness. Findings suggest specific prevention strategies to protect the health conditions of Italian workers and may offer useful information to drive national policy implementation in the OSH field.